The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/17450128.2017.1308045
|View full text |Cite
|
Sign up to set email alerts
|

Parent healthful eating attitudes and motivation are prospectively associated with dietary quality among youth with type 1 diabetes

Abstract: A family-based behavioral nutrition intervention grounded in Social Cognitive and Self-Determination Theories showed an increased intake of whole plant foods. This study examined 1) whether the intervention changed parent diet-related attitudes/beliefs, 2) whether these attitudes/beliefs were associated with youth diet quality, and 3) the moderating roles of youth age and parent nutritional knowledge. Youth with type 1 diabetes and their parents (n = 136, mean ± SD youth age = 12.6 ± 2.8 years) participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…Although considerable discussion has focused on the influence of parental nutrition knowledge, less research has focused on the effects of parenting attitudes on their offspring’s food consumption, nutritional habits, and diet quality. Our findings agree with a recently published randomized controlled trial of a family-based behavioral nutrition intervention [20] in children with type 1 diabetes that concluded that parents’ diet-related attitudes and beliefs were linked to their children’s diet quality, remarking on the essential role of parental psychosocial factors.…”
Section: Discussionsupporting
confidence: 92%
“…Although considerable discussion has focused on the influence of parental nutrition knowledge, less research has focused on the effects of parenting attitudes on their offspring’s food consumption, nutritional habits, and diet quality. Our findings agree with a recently published randomized controlled trial of a family-based behavioral nutrition intervention [20] in children with type 1 diabetes that concluded that parents’ diet-related attitudes and beliefs were linked to their children’s diet quality, remarking on the essential role of parental psychosocial factors.…”
Section: Discussionsupporting
confidence: 92%
“…Diet quality resemblance at final study: HEI (β (SE) = 0.29 (0.11), p = 0.009) of the intervention group WPFD (β (SE) = 0.33 (0.09), p < 0.001) of the intervention group Nansel et al [ 29 ] N = 66 intervention N = 70 control 8–16 years Behavioral nutrition intervention to increase whole plant foods HEI-2005 WPFD Pickiness subscale of the Child Feeding Questionnaire The intervention effect on diet quality was positive for picky eaters only (WPFD p < 0.001; HEI p = 0.04). Eisenberg-Colman et al [ 30 ] N = 42 intervention N = 48 control 8–16 years Behavioral nutrition intervention to increase whole plant foods Adherence to diabetes management tasks Disordered eating behaviors (DEB) DEPS-R Intervention on DEB: β (SE) = 0.00 (0.00), p = 0.84 DEPS-R vs. diabetes management: β (SE) = −0.20 (0.09), p = 0.03 Eisenberg et al [ 31 ] N = 66 intervention N = 70 control 8–16 years Behavioral nutrition intervention to increase whole plant foods Dietary intake Whole Plant Food Density (WPFD) Self-Efficacy for Healthy Eating Outcome Expectations for Healthy Eating Barriers to Healthy Eating Treatment Self-Regulation Parent Nutrition Knowledge Parent self-efficacy vs. WPFD ( β = 0,21, p = 0.02) Autonomous motivation vs. WPFD ( β = 0.17, p = 0.002) Nutrition knowledge vs. WPFD ( β = 0.01, p = 0.03) Barriers to Healthy Eating vs. WPFD ( β = −0.19, p = 0.02) Negative Outcomes Expectation vs. WPFD ( β = −0.20, p = 0.008) Parent positive outcome expectations vs. WPFD ( β = 0.07, p = 0.45) Controlled motivation vs. WPFD ( β = −0.03, p = 0.56) Gilbertson et al [ 27 ] N = 38 CHOx group N = 51 low-GI group 8–13 years Comparison between the CHOx with low-GI Macronutrient intake Carbohydrate food sources Carbohydrate distribution of meals and snacks Energy intake (MJ/day): CHOx group vs. low-GI group (mean (SD) = 9.1 (1.7) vs. 9.3 (1.4), respectively). Protein (%): CHOx group vs. low-GI ...…”
Section: Resultsmentioning
confidence: 99%
“…In terms of DSMES, a post-hoc analyses of a RCT performed to assess the relationship between parent attitudes and youth diet quality, described no effect of the intervention on parent attitudes or beliefs [ 30 ]; however, a higher parent self-efficacy and autonomous motivation were positively associated with those youth with a higher adherence to a WPFD diet. Furthermore, a secondary data analysis from this RCT found that a behavioral intervention to improve dietary quality did not increase disordered eating behaviors in adolescents [ 29 ]; nevertheless, a greater adherence to diabetes self-management was associated with lower diabetes eating problems in adolescents with type 1 diabetes [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we observed that autonomous motivation was associated with healthful eating in this sample, while controlled motivation was not (34). Taken together, findings indicate differential roles of autonomous and controlled motivation in healthful eating versus DEB.…”
Section: Discussionmentioning
confidence: 49%